From Restrictive to Prescriptive? Prospects for China’s Church Engaging with the Civil Society - Woods, Paul (Transformation, 2016)
China’s civil society has expanded recently, providing space for new players, although it remains small and controlled by the Communist Party. The mainland Chinese church is taking its place in the civil society, although it is unlikely that it will enjoy Western-style freedoms even in the medium term. Singapore is an Asian democracy where relations between church and civil society are different again; the country has long been culturally and religiously pluralist, and was never part of ‘Christendom’. Also, Singapore’s government is more socially interventionist than its Western counterparts. I describe the West, Singapore and China as permissive, prescriptive and restrictive, respectively, and conclude that Singapore’s prescriptive approach to church and civil society may be a model for China.